Rehabilitation Arrangements In The Narcotics Crime Law In The Perspective Of Criminal Law Reform - Kadek Widhiantari Ningsih; I Nyoman Gede Sugiartha; I Made Arjaya (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2023)
There are conflicting norms (conflict norms) in Article 4 and Article 54 of the Narcotics Law which essentially guarantees rehabilitation for narcotics abusers for themselves, however in Article 127 of the Narcotics Law the threat of imprisonment is at the same time that the act also meets the qualifications for the act as regulated in Articles 111 and/ or Article 112 or even Article 114 of the Narcotics Law. These conditions are the background for this research in order to analyze (1) the regulation of the rights of Indonesian citizen workers and citizen workers which are considered by judges to decide on rehabilitation sanctions or prison sanctions for narcotics users or addicts; and (2) regulation of sanctions for future narcotics users or addicts (ius constituendum). The research method used is a type of normative legal research with a statutory approach and a conceptual approach. The research results show (1) The judge's considerations in deciding on rehabilitation sanctions or imprisonment for narcotics users or addicts include juridical considerations, especially Article 54 of the Narcotics Law which requires narcotics addicts and victims of narcotics abuse to undergo medical rehabilitation and social rehabilitation. If the judge cannot apply the applicable law, in this case the Narcotics Law, then the judge is obliged to find the law in order to achieve a fair decision; and (2) Regulation of sanctions for narcotics users or addicts in the future (ius constituendum) prioritizing rehabilitation sanctions which can be used as depenalization efforts as well as legal protection for narcotics addicts in order to optimize sanctions which so far have not been effective in preventing and overcoming narcotics abuse, so that the only The only way to cure it is to undergo rehabilitation.